Ant Colony Algorithms For The Vehicle Routing Problem With Time Window, Period And Multiple Depots - Agardi, Anita; Kovacs, Laszlo; Banyai, Tamas (Manufacturing Technology Journal, 2021)
Vehicle Routing Problem is a common problem in logistics, which can simulate in-plant and out-plant material handling. In the article, we demonstrate a Vehicle Routing Problem, which contains period, time window and multiple depots. In this case, customers must be served from several depots. The position of the nodes (depots and customers), the demand and time window of the customers are known in advance. The number and capacity constraint of vehicles are predefined. The vehicles leave from one depot, visit some customers and then return to the depot. The above-described vehicle routing is solved with construction algorithms and Ant Colony algorithms. The Ant Colony algorithms are used to improve random solutions and solutions generated with construction algorithms. According to the test results the Elitist Strategy Ant System and the Rank-Based Version of Ant System algorithms gave the best solutions.
Keywords: vehicle routing problem; ant colony algorithms; improvement algorithms; construction algorithms